Risk Measurement of Stocks Using Value at Risk with Johnson Transformation - Sulistianingsih, Evy (2022)
This paper utilizes Johnson Value at Risk (JoVaR) to evaluate the individual risk of Indonesian five stocks listed in the LQ-45 Index (period of February 2021 until July 2021). The stocks are Aneka Tambang Tbk (ANTM), PT. Bank Central Asia Tbk (BBCA), PT. Indofood Sukses Makmur Tbk (INDF), Perusahaan Perseroan (Persero) PT. Telekomunikasi Indonesia Tbk (TLKM), and PT. Semen Indonesia (Persero) Tbk (SMGR). According to the result of the analysis, it can be concluded that the maximum potential loss of BBCA, ANTM, TLKM, INDF, and SMGR when the assets were held for one day for the next period of investment is between 2.56 percent until 4.48 percent, with 95 percent confidence level. Based on Kupiec Backtesting, for several confidence levels, it can also be summarized that JoVaR more effectively measures the risk than historical VaR. © 2022 American Institute of Physics Inc.. All rights reserved.